New cyanobacterium Aliterella vladivostokensis sp. nov. (Aliterellaceae, Chroococcidiopsidales), isolated from temperate monsoon climate zone (Vladivostok, Russia) - Abdullin, Shamil R.; Nikulin, Arthur Yu.; Bagmet, Veronika B.; Nikulin, Vyacheslav Yu.; Gontcharov, Andrey A. (Phytotaxa, 2021)
A new coccoid cyanobacterium Aliterella vladivostokensis sp. nov. was described from an urban aerophytic habitat in a temperate monsoon climate (Vladivostok, Russia) using a polyphasic approach. Phylogenetic analyses based on the 16S rRNA gene sequences confirmed that our isolate was a member of the Aliterella genus clade. Aliterella species are hardly distinguishable from each other morphologically and were described from highly contrasting natural and artificial environments with only a few records from several continents. Despite high similarity of morphometric data for A. vladivostokensis and A. antarctica cells and a compensatory base change in the D1–D1′ helix shared by these species; high percent of dissimilarity (11.6±1.3) between their 16S–23S internal transcribed spacer sequences with at least 5 autapomorphic mutations in the D1–D1′ and Box-B helices, and distinct folding patterns of the Box-B helix allowed us to erect a new species.